In silico Approach Revealed α-amylase Inhibitor of Sappanon Compounds From Caesalpinia sappan In Carbohydrate Metabolism : Kajian in silico Senyawa Sappanon Caesalpinia sappan Sebagai Inhibitor α-amylase Pada Metabolisme Karbohidrat - Dewi Ratih Tirto Sari; Siti Zamilatul Azkiyah; M. Eko Pranoto; Yohanes Bare; Lailatus Sarifah (Akademi Farmasi Surabaya, 2023)
Human salivary amylase is a hydrolase enzyme that hydrolyze polysaccharides to small sugar. The α- amylase inhibition is an alternative strategy for reducing hyperglycemia. Caesalpinia sappan heartwood contains several bioactive compounds, as sappanon and derivates. Those compounds have been reported for promoting PDE4 inhibitor and anti-inflammatory. This study compared the α- amylase antagonist effect of sappanone A, Sappanone B, 3′-Deoxysappanone A, 3-Deoxysappanone B, and Neosappanone A compounds through molecular docking. In silico approach was used to identified the potential activity of those compounds. Five sappanone compound and their derivates were taken out the 3D structure at PubChem NCBI database. Then the α- amylase structure also was downloaded from Protein Data Bank with PDB ID 1smd. Among five sappanon compounds, L-peptide linking (control) and α- amylase were redocked using Molegro virtual docker and then visualized by Discovery studio version 5.50. The 3D complex structure of five sappanone compounds and their derivates showed inhibition activity of α- amylase at the same site of L-peptide linking. LYS227 was identifies in five sappanon - α-amilase complex. The ILE230 also showed in the complex of Neosappanone A, Sappanone B, and 3-Deoxysappanone B. interestingly, the ASN250 performed at Sappanone A and Sappanone B. in conclusion, this study suggests that five sappanone compounds and derivates potentially as antihyperglycemic and prevent the diabetes mellitus type 2 syndrome.